(untitled) (Revista Contexto & Educação, 2024)
Teaching has been an experience marked by suffering and illness. These processes are closely related to emotions, so that emotional development is a protective factor for mental health. Psychology can articulate practices with the objective of the emotional development of teachers when it is attentive to the multiple determinations that give rise to the most diverse emotions. The objective of this paper is to analyze the work of school and educational psychologists from SEDUC-CE about their work with high school teachers regarding the emotional development of these professionals. The psychologists’ work is characterized by the contradiction between reproductive practices, which do not contribute to the emotional development of teachers, and transformative practices, which contribute to it.